PENINGKATAN KEMAMPUAN MENGURAIKAN STRUKTUR SURAT DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GAME INTERAKTIF PUZZLE RACE PADA SISWA KELAS VII F SMP NEGERI 6 MADIUN - Kamalin Naufi Hidaya; Ermi Adriani Meikayanti; Eriana Widya Rahmawati (STKIP Subang, 2026)
This research was motivated by students' difficulty in analyzing letter structures. Therefore, it is necessary to find a solution to overcome this problem by providing a problem-based learning model assisted by an interactive puzzle race game. The method applied was Classroom Action Research (CAR). The research subjects were 30 students in grade VII F. Based on observations from the pre-action cycles 1 and 2, there was an increase: pre-action student completeness was only 6%, cycle 1 experienced an increase of 80%, and cycle 2 experienced an increase of 100%. In conclusion, the use of a problem-based learning model assisted by an interactive puzzle race game can improve students' ability to analyze letter structures.